Preliminary studies into polypropylene composites reinforced with fruit waste biomass: a choice towards sustainability - Sharma H.; Gairola S.; Misra J.P.; Singh I. (My University, 2025)
The development of polypropylene (PP) composites filled with a biomass from fruit waste, citrus limetta peel (CLP) fillers is explored in the current study. A polymer matrix consisting of neat polypropylene was filled with 10, 20, and 30% weight percentage (w/w) of CLP. The composite specimens were produced by extrusion followed by injection moulding. In addition to thermal and morphological evaluations, the mechanical properties are determined, including tensile and flexural (both strength and modulus). The primary results demonstrate that, for a 10 weight percent filler content, the inclusion of CLP filler raised the tensile and flexural modulus of the neat PP composites by 20.23% and 14.33%, respectively. All of the composites were found to be thermally stable up to 220 °C through thermal investigation. The burning rate increased with the incorporation of fillers whereas, the dripping effect gets reduced. Filler agglomeration, filler pull out, and poor adherence with increased CLP filler content were observed using scanning electron microscopy. The developed composites have got tremendous potential to be utilized in non-structural applications. The consequences of plastic burden on the environment can also be reduced. © 2024 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.